Impacts of post-Brexit agricultural policy on fruit and vegetable intake and cardiovascular disease. (13th November 2019) - Seferidi, P; Laverty, A A; Pearson-Stuttard, J; Collins, B; Bandosz, P; Capewell, S; O'Flaherty, M; Millett, C
Abstract: Background: The post-Brexit agricultural regime represents an opportunity to positively influence food systems and improve public health. Health-improving measures could include expanding the UK production of fruits and vegetables (F&V), thus increasing F&V availability. Currently, only 1.4% of total agricultural land in England is allocated to F&V. This study aims to estimate the potential impacts of allocating additional land to F&V production on cardiovascular disease (CVD) and inequalities in England between 2021 and 2030. Methods: We used the previously validated IMPACT Food Policy model to translate changes in land allocated to F&V into changes in F&V intake and associated CVD mortality, expressed in number of deaths prevented or postponed (DPPs) by age, sex, and Index of Multiple Deprivation (IMD) quintile. We modelled two scenarios that assumed a linear increase in agricultural land allocated to F&V until it covers a) 10% and b) 20% of all land suitable for production of horticultural crops in England. We assumed that F&V prices would drop to a new equilibrium. We used Monte Carlo simulations to produce uncertainty intervals. Results: Our model suggested that by 2030, F&V intake might increase by approximately 4% (95% Uncertainty Interval: 2%-7%) and 8% (4%-13%) respectively, under the first scenario. Under the second scenario, F&V intake could increase by approximately 17% (10%-29%) and 37% (26%-51%) respectively. These increases in F&V intake were associated with 3360 (1760-5920) CVD DPPs under the first scenario and 15700 (9000-24310) under the second scenario in 2021-2030. Our modelled scenarios could also reduce inequalities, with some 16% of DPPs occurring in the least deprived group compared with 22% in the most deprived. Conclusions: Policymakers should consider the public health impacts of the post-Brexit agricultural regime in England. Increasing the land allocated to F&V production could substantially reduce the burden of CVD and associated inequalities. Key messages: The post-Brexit agricultural policy can be an opportunity to improve diet and public health in the UK. Increasing the agricultural land allocated to fruit and vegetable production in England could reduce the burden of cardiovascular disease and associated inequalities.